Disability and prognostic factors of MS severity: An Algerian cohort study - N., HECHAM; M., TAZIR (Journal of Neurological Research And Therapy, 2023)
Background The evolution of multiple sclerosis (MS) is highly variable. Predicting this evolution at the beginning of the disease will help in the therapeutic management. The objective of this study was to describe the clinical characteristics and to identify early predictors of long-term disability among MS patients in Algeria. Methods We performed a descriptive and retrospective study of 400 MS patients followed over a 4-years period from July 2012 to July 2016 in the neurology department of Mustapha Bacha hospital in Algiers. The following parameters were systematically assessed for each patient: Age at onset, gender, relapses, initial demyelinating event, interval between first and second attack, residual deficit after first attack, onset of the progressive course, time of assignment of the successive scores of irreversible disability and type of disease modifying therapies. Univariate and multivariate Cox models were used to determine factors influencing time to Expanded Disability Status Scale (EDSS) 4 and 6. Results During the follow-up of this cohort of MS patients, a total of 144 (36%) and 83 (20%) patients reached EDSS scores 4 and 6 respectively. The median times from the onset of MS to assignment of a score 4 and 6 was 10 years and 19 years, respectively. Using the MSSS severity score, and after univariate analysis we identified several risk factors predictive of disease severity. These included male sex (P= 0.002), age of onset ≥ 40 years (P= 0.001), pyramidal (P= 0.0001), cerebellar (P= 0.002), and poly-symptomatic (P=0.0001) onset of the disease, incomplete recovery after the first attack (P= 0.0001), a high number of attacks during the first 2 years (P= 0.04) and the progressive form (P=0.001), and all these factors were correlated with a high MSSS score. However, prognostic factors in the multivariate binomial logistic regression analysis were limited to pyramidal onset, incomplete recovery after the first attack, short interval between the first and second attack, and progressive onset. Conclusion On the whole, the early predictive factors of disability in MS among Algerian patients were age of onset over 40 years, pyramidal onset, incomplete recovery after the first attack, short interval between the first and second attack and progressive form at onset. To increase the generalizability of findings, a national MS registry is strongly recommended, as well as long-term follow-up epidemiological studies.
Keywords: Multiple sclerosis; disability; progression